Literatura surda: o que sinalizam professores surdos sobre livros digitais em Língua Brasileira de Sinais - LIBRAS - Rosa, Fabiano Souto (2011)
This research analyzes what deaf teachers think about digital books in Brazilian Sign Language - LIBRAS. There are several materials available in LIBRAS, but my focus is only on digital books. For this, we selected six stories in digital format, signalized in LIBRAS (among them translations, adaptations and productions) and presented for six deaf teachers from different regions of Rio Grande do Sul State. These selected teachers have training in education, they were students of LIBRAS Language, and act as LIBRAS teachers in different educational levels. These Educators watched the videos and they signaled their impressions based on questions that explored the technical part of the video, signaling brands present in deaf history and its importance when used for deaf children Education. To conduct this research, I relied on Cultural Studies and Deaf Studies, realizing the Deaf Literature as part of Deaf Culture and indispensable for the acquisition of a deaf identity. From the interviews, various opinions which point to a new moment in the lives of deaf and also some major changes when they think of producing new stories in LIBRAS, contributing to improve the Deaf Literature available in our country